2005
DOI: 10.4049/jimmunol.175.5.3207
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial NK Cell-Derived IL-13 Induces Intestinal Pathology Associated with Nematode Infection

Abstract: IL-13 is a Th2-derived cytokine associated with pathological changes in asthma and ulcerative colitis. Moreover, it plays a major role in the control of gut nematode infection and associated immunopathology. The current paradigm is that these effects are due to T cell-derived IL-13. We show in this study that an innate source of IL-13, the intraepithelial NK cell, is responsible for the disruption of intestinal tissue architecture and induction of goblet cell hyperplasia that characterizes infection with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 50 publications
6
72
1
Order By: Relevance
“…Taken together, our results indicate that the IL-13-producing DX5 + cells are NK cells, since they expressed IL-2Rb, CD11b and Ly49C but not FceRI, c-kit or TCR. It has consistently been reported that NK cells are an important source of IL-13 in vitro and in vivo [17,46,47]. In particular, our findings demonstrate that NK cells express IL-13 as well as IFN-c in vivo during infectious disease.…”
supporting
confidence: 80%
“…Taken together, our results indicate that the IL-13-producing DX5 + cells are NK cells, since they expressed IL-2Rb, CD11b and Ly49C but not FceRI, c-kit or TCR. It has consistently been reported that NK cells are an important source of IL-13 in vitro and in vivo [17,46,47]. In particular, our findings demonstrate that NK cells express IL-13 as well as IFN-c in vivo during infectious disease.…”
supporting
confidence: 80%
“…Intestinal pathology in our model infection appeared as increased cellular infiltration of the lamina propria and a disturbed architecture of the intestinal epithelium with villus atrophy and crypt hyperplasia. For infections with T. spiralis it has been shown that IL-13 is responsible for villus atrophy as well as crypt and goblet cell hyperplasia [35]. Hence, we speculate that the increased IL-13 response in Figure 6.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, these treated mice showed an elevation in NK cells within the MLN. These cells are a well-characterized source of IFN-␥ (37) and have previously been demonstrated in SCID mice to be responsible for the disruption of intestinal tissue architecture in the context of infection with the intestinal helminth Trichinella spiralis, although in this case via the cytokine IL-13 (38). Whether IL-33's ability to alter inflamed tissue in a non-T cell manner and the direct effects this cytokine has on T cell polarization are functions that influence one another remains to be resolved.…”
Section: Discussionmentioning
confidence: 99%